Programa Basado En El Deporte Para La Intervención En Situaciones De Agresión En Los Niños Pertenecientes Al Centro De Estudios Y Prácticas Académicas Y Sociales (C.E.P.A.S) De La Universidad Del Quindío (2014)
This project's main objective was to promote the control of aggressive situations with a sports program for children of the Center for Academic and Social Studies and Practices of the University of Quindío. The population of children and adolescents of the Center of Studies and Academic and Social Practices (C.E.P.A.S.) Pro-child, of the University of Quindío, to which the sport-based program was to intervene in situations of aggression constituted , approaches based on individual and team sport, aggression and their types, intervention from the sport and the different theoretical references which suggest that sport can be a mediator for channeling behavior or aggressive situations, for the veracity of the project in reference to the population applied the scale of aggression among peers, which provided us with information before and after the program execution, once the scale applied proceeded to perform a proper analysis of the data which indicate that there was a benefit in decreasing aggression from the implementation of the program based on the sport in situations of aggression, with its themes are provided tools through sport. Finally there was an emphasis on the continuity of programs like this to promote healthy lifestyles and physical activity to children and adolescents, as well, with staff that is part of the Center of Studies and Academic and Social Practices (C.E.P.A.S.).